Supercapacitors based on two dimensional VO2 nanosheet electrodes in organic gel electrolyte. (1st December 2016) - Rakhi, R.B.; Nagaraju, D.H.; Beaujuge, Pierre; Alshareef, H.N.
Graphical abstract: (a) CVs of solid state device measured at different angles (inset shows the schematic for the measurement of the bending angles and the optical image of the flexible supercapacitor device). (b) Optical images displaying lighting up of an LED using three flexible supercapacitors connected in series. Highlights: Synthesis of 2D VO2 nanosheets by hydrothermal reduction of V2 O5 nanopowder. A specific capacitance of 405 F g −1 in organic electrolyte at 1 A g −1 . An energy density of 46 Wh kg −1 at 1 Ag −1 for VO2 based symmetric capacitor. Fabrication of all solid state flexible supercapacitors. Series combination of three solid state capacitors lighting up an LED for 1 minute. Abstract: VO2 is a low band-gap semiconductor with relatively high conductivity among transition metal oxides, which makes it an interesting material for supercapacitor electrode applications. The performance of VO2 as supercapacitor electrode in organic electrolytes has never been reported before. Herein, two-dimensional nanosheets of VO2 are prepared by the simultaneous solution reduction and exfoliation from bulk V2 O5 powder by hydrothermal method. A specific capacitance of 405 Fg −1 is achieved for VO2 based supercapacitor in an organic electrolyte, in three electrode configuration. The symmetric capacitor based on VO2 nanosheet electrodes and the liquid organic electrolyte exhibits an energy density of 46 Wh kg −1 at a power density of 1.4 kW kg −1 at a constant current density of 1 Ag −1 . Furthermore, flexible solid-state supercapacitors are fabricated using same electrode material and Alumina-silica based gel electrolyte. The solid-state device delivers a specific capacitance of 145 Fg −1 and a device capacitance of 36 Fg −1 at a discharge current density of 1 Ag −1 . Series combination of three solid state capacitors is capable of lighting up a red LED for more than 1 minute.